2019
DOI: 10.1007/s40520-019-01183-w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment in primary care: a systematic review

Abstract: Background Comprehensive geriatric assessment (CGA) involves the multidimensional assessment and management of an older person. It is well described in hospital and home-based settings. A novel approach could be to perform CGA within primary healthcare, the initial community located healthcare setting for patients, improving accessibility to a co-located multidisciplinary team. Aim To appraise the evidence on CGA implemented within the primary care practice. Methods The review followed PRISMA recommendations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 26 publications
(75 reference statements)
5
82
0
7
Order By: Relevance
“…The discriminative ability of several screening instruments to identify older persons at increased risk of functional decline and mortality ranges from 0.60 to 0.80 in the literature, which are very similar to those demonstrated by our study [4,[15][16][17][18][19][20]. However, none of these instruments have been evaluated in the context of resource-limited primary care settings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The discriminative ability of several screening instruments to identify older persons at increased risk of functional decline and mortality ranges from 0.60 to 0.80 in the literature, which are very similar to those demonstrated by our study [4,[15][16][17][18][19][20]. However, none of these instruments have been evaluated in the context of resource-limited primary care settings.…”
Section: Discussionsupporting
confidence: 86%
“…However, the evidence concerning the benefits of applying the broad principles of CGAs in primary care are controversial [3]. In a recent systematic review, CGAs based on primary care practice were acceptable to the individuals involved but had an inconsistent impact on mortality, functional status and hospital admission rates [4]. Moreover, there is a need for new models that address the complexity of care of older adults living with multimorbidity or frailty in primary care, as these models can lead to quality of care improvements without increases in costs [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A recent systematic review of comprehensive geriatric assessments in primary care also reported only limited benefits for patients. 37 NHS England have recommended further research based on the potential benefits for some critical outcomes, 38 but we are currently far from having a clear insight into approaches that work and for whom.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…The assessment of older patients is carried out in some geriatric day hospitals, especially for complex cases. New organizations for a geriatric assessment are proposed, to allow its realization in primary care [80,81]. The geriatric assessment could be realized for example by a trained nurse in the patient's home or in multi-professional primary care health centers with good results [82].…”
Section: Comparison With Frail Individuals Aged 65 and Overmentioning
confidence: 99%